2018
DOI: 10.1371/journal.pone.0203717
|View full text |Cite
|
Sign up to set email alerts
|

Cariogenic potential of sweet flavors in electronic-cigarette liquids

Abstract: BackgroundMost electronic-cigarette liquids contain propylene glycol, glycerin, nicotine and a wide variety of flavors of which many are sweet. Sweet flavors are classified as saccharides, esters, acids or aldehydes. This study investigates changes in cariogenic potential when tooth surfaces are exposed to e-cigarette aerosols generated from well-characterized reference e-liquids with sweet flavors.MethodsReference e-liquids were prepared by combining 20/80 propylene glycol/glycerin (by volume fraction), 10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 80 publications
3
82
0
2
Order By: Relevance
“…There are currently over 10 000 commercially available e‐liquid formulations 7 (Table 1). These formulations basically have three components: a base, nicotine, and flavors.…”
Section: Background Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…There are currently over 10 000 commercially available e‐liquid formulations 7 (Table 1). These formulations basically have three components: a base, nicotine, and flavors.…”
Section: Background Informationmentioning
confidence: 99%
“…The sweet taste of e‐liquids is provided by the inclusion of sucrose or sucralose and the sweet fragrance is created by ethyl maltol. in vitro studies have shown that some of these flavors significantly promote increased biofilm formation and enamel demineralization compared to a base/nicotine control, when used in vaping devices 7 . It is believed that the sweet flavors have been added to e‐liquids to make them especially attractive to young people.…”
Section: Background Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has found that EC aerosols have similar chemical properties to high-sucrose, gelatinous and acidic drinks (Kim et al, 2018).…”
Section: Smokers' and Non-smokers' Accounts Of E-cigarettes 12mentioning
confidence: 99%
“…Fewer than 50% of cultures from actinomyces-related infections manage to isolate a species; as a result many diagnoses rely on histopathological visualisation of actinomyces over microbiological isolation. 1 A fit and healthy 33-year-old male attended our oral surgery unit with a history of tightness in his left jaw and no other symptoms.…”
Section: A Difficult Diagnosismentioning
confidence: 99%